Motility and Abnormality of Sheep Spermatozoa That is Being Frozen Using Soybean Lecithin (Soybean Lecithin) - Salmin Salmin; Marsudi Marsudi; Hendro Sukoco; Deka Uli Fahrodi (Journal Research of Social Science, Economics, and Management, 2021)
The specific purpose of this study was to determine the effect of optimal levels of soybean lecithin in sperm extenders on motility and abnormalities of sheep spermatozoa after undergoing the freezing process. This research was conducted experimentally in a laboratory with a completely randomized design (CRD) with five treatments and three replications. The five treatments tested were soybean lecithin levels in Tris (L) diluent, consisting of: L0 = 0% soybean lecithin + 95% Tris diluent + 5% glycerol; L1 = 1% soy lecithin + 94% Tris diluent + 5% glycerol; L2 = 2% soy lecithin + 93% Tris diluent + 5% glycerol; L3 = 3% soy lecithin + 92% Tris diluent + 5% glycerol; L4 = 4% soy lecithin + 91% Tris diluent + 5% glycerol. The independent variable in this study was the level of soy lecithin in the Tris diluent. The dependent variable is the progressive motility and abnormalities of post-clotting spermatozoa. Soybean lecithin levels had a significantly different effect (P?0.05) on the percentage of progressive motility and spermatozoa abnormalities of post-freezing sheep. The level of 3% soya bean lecithin is the best level in maintaining the quality of post-freezing sheep spermatozoa.